The Sparta and the Athens Of Our Age At Daggers Drawn: Polities, Perceptions, and Peace - Rendall, Matthew (Palgrave Macmillan Ltd., 2004)
While historically notions of democracy have varied widely, democratic peace theory has generally defined it in procedural terms. This article takes a close look at the Anglo-French confrontation of 1840. I show that while leaders on both sides were prepared to risk war to gain bargaining advantages, only the French left really wanted to fight. Why? By today's criteria, Britain was incontestably more democratic, with its monarch's powers far more restricted and its suffrage several times as large. Nevertheless, both sides considered France more democratic, with French republicans despising Britain as an aristocratic oligarchy. While Spencer Weart is right to argue that democratic republics may be hostile to oligarchic ones, they will not necessarily define each other according to modern procedural criteria. Instead, they may judge regimes by the broader social structures that shape power relationships and by outcomes, possibly explaining wars or near misses between democracies.